PENGARUH SOSIAL MEDIA TERHADAP BRAND AWARENESS AMARIS HOTEL - Sofiani, Sofiani (Kepariwisataan: Jurnal Ilmiah, 2020)
Social media has became one of the marketing strategies by most of the companies to deliver their brands, products and services to customer. Apart from the advantages of the use of social media for companies, it is becoming difficult for companies to raise awareness for their brand beause of the competition. The aim of this research is to determine the impact of social media on brand awareness of Amaris Hotel. The results of this research obtained from questionnaires that had been distributed to the respondents in Jakarta and processed with correlation method. The results shows that social media gives quite big and positive impact on building and estabilishing brand awareness of AYANA Amaris Hotel for 41,5%, and Instagram gives the biggest impact on brand awareness of Amaris Hotel. The level of brand awareness of Amaris Hotel has reached the highest level, Top of Mind level. Keywords: Social Media, Brand Awareness, Marketing, Amaris Hotel